Dissonance and the Drama of Divine Sovereignty in the Book of Daniel. By Amy C. Merrill Willis - Davies, Philip R. (The journal of theological studies, 2011)
This book examines divine power and presence within the visionary chapters of the book of Daniel. Written in a time of deep political and religious crisis, Daniel seems to assert divine sovereignty, yet divine action is scarcely described, and becomes increasingly limited to the eschaton, highlighting divine abstention from history and from the present. This problem has already been noted by several scholars but deserves a detailed treatment at the level of theology and of social history., The problem having been formulated in chapter 1, Willis analyses Daniel 2, 7, 8, 9 and 10–12, finding a slightly different, and evolving, perspective in each.